MAJELIS TA'LIM: Strategi Dakwah Dalam Mempererat Ukhuwah Islamiyah - Suriati Suriati (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
Majelis Ta'llm (Islamic study group) is a non-formal da'wah institution and forum to empower Muslim community. In practice, Majelis Ta'lim is a place to spread Islamic da'wah and symbols which are flexible and time-unlimited. It is also open to Muslims from all social strata, gender, and age. Time to hold Islamic studies in Majelis Ta'lim is not limited, it can be hold anytime, and the place can be anywhere-house, mosque, and so on. In addition, Majelis Ta'lim has two functions as a non-formal da'wah and educational institutions. It is this flexibility that make this institution survive and become a da'wah institution which is close to Muslim community. Here is the strategic value of Majelis Ta'lim as a forum of Muslims' gathering to do a myriad of activities. On the other hand, this gathering will strengthen a psychological relationship between members of Islamic study group, which will in tum establish Islamic brotherhood among them.